2013
DOI: 10.1038/ncomms4017
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of AMPK regulation by small molecule activators

Abstract: AMP-activated protein kinase (AMPK) plays a major role in regulating cellular energy balance by sensing and responding to increases in AMP/ADP concentration relative to ATP. Binding of AMP causes allosteric activation of the enzyme and binding of either AMP or ADP promotes and maintains the phosphorylation of threonine 172 within the activation loop of the kinase. AMPK has attracted widespread interest as a potential therapeutic target for metabolic diseases including type 2 diabetes and, more recently, cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
608
5
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(644 citation statements)
references
References 59 publications
29
608
5
2
Order By: Relevance
“…Accordingly, active research is ongoing to identify small-molecule activators of AMPK (82,83). However, to our knowledge, physiological small-molecule activators of AMPK, other than AMP, are not known.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, active research is ongoing to identify small-molecule activators of AMPK (82,83). However, to our knowledge, physiological small-molecule activators of AMPK, other than AMP, are not known.…”
Section: Methodsmentioning
confidence: 99%
“…A769662 is a direct and specific activator of AMPK, which binds in the interface between the AMPK α-and β-subunits and allosterically activates the complex (32). We therefore tested A769662 in HUVEC and found that it inhibited proliferation with an IC 50 of 73 μM (±8.34; SEM) (SI Appendix, Fig.…”
Section: Knockdown Of Vdac1 In Huvec Phenocopies the Effects Of Itracmentioning
confidence: 99%
“…Only AMP binding at CBS site 3 is shown (marked as AMP-3). Reprinted with permission from Macmillan Publishers Ltd: [Nature] (Xiao et al, 2013), (http://creativecommons.org/licenses/by/3.0/legalcode). (B) The a-subunit is a 550 amino acid long catalytic subunit and is composed of the kinase domain, a-linker region, the C-terminal b/g-subunit interacting domain (a-CTD), and a nuclear export signal.…”
Section: General Introductionmentioning
confidence: 99%
“…Additionally, this region is also involved in the interaction of the a-subunit kinase domain with the regulatory fragment, which consists of the C-terminal domains of the a-and b-subunits and all domains of the g-subunit (Momcilovic et al, 2008;Xiao et al, 2011Xiao et al, , 2013. More recently, the CBM region was also shown to be involved in protecting AMPK from cellular phosphatases (Xiao et al, 2013), such as human protein phosphatase-2ca (PP2Ca) (Davies et al, 1995). In fact, the CBM region binds to the N-lobe of the kinase domain and is also connected to the regulatory fragment (Xiao et al, 2013).…”
Section: General Introductionmentioning
confidence: 99%
See 1 more Smart Citation